A concise review of extraction and characterization of chondroitin sulphate from fish and fish wastes for pharmacological application - Urbi, Zannat; Nina Suhaity, Azmi; Long, Chiau Ming; Hossain, Md. Sanower (MDPI, 2022)
Chondroitin sulphate (CS) is one of the most predominant glycosaminoglycans (GAGs) available in the extracellular matrix of tissues. It has many health benefits, including relief from osteoarthritis, antiviral properties, tissue engineering applications, and use in skin care, which have increased its commercial demand in recent years. The quest for CS sources exponentially increased due to several shortcomings of porcine, bovine, and other animal sources. Fish and fish wastes (i.e., fins, scales, skeleton, bone, and cartilage) are suitable sources of CS as they are low cost, easy to handle, and readily available. However, the lack of a standard isolation and characterization technique makes CS production challenging, particularly concerning the yield of pure GAGs. Many studies imply that enzyme-based extraction is more effective than chemical extraction. Critical evaluation of the existing extraction, isolation, and characterization techniques is crucial for establishing an optimized protocol of CS production from fish sources. The current techniques depend on tissue hydrolysis, protein removal, and purification. Therefore, this study critically evaluated and discussed the extraction, isolation, and characterization methods of CS from fish or fish wastes. Biosynthesis and pharmacological applications of CS were also critically reviewed and discussed. Our assessment suggests that CS could be a potential drug candidate; however, clinical studies should be conducted to warrant its effectiveness.